RANCANG BANGUN SMART AIR PURIFIER (SOFTWARE) - Muhammad Femi; Wahyuni Khabzli (Politeknik Caltex Riau, 2021)
Humans unconsciously breathe dirty air every day and as a result, the dirty air enters the human body so that the air-related disease will occur to those who breathe it. To avoid this, one way to prevent this is to know how the surrounding air is and how to deal with dirty air by being in a closed room where the air is clean inside so that dirty air outside does not enter the body which results in disturbed breathing. So that in this final project a Smart Air Purifier will be designed to handle air contaminated with PM10. For the author's focus here is the creation of a system from a smart air purifier and connected to the firebase database for data storage from the GP2Y1010AU0F sensor and DHT11 sensor as well as to control several components such as relays, fans and ionizers and the monitoring and control process of this device through an existing android application Connect to Firebase servers using Android Studio. The average error percentage value from the PM10 sensor reading is 13.47%. For the control section, the device is running well according to user needs. With this application, it is hoped that it can make it easier for users to control devices remotely and monitor the air condition of a room so that the air in a room becomes clean and good for humans.